Health Belief Model-based intervention to improve nutritional behavior among elderly women - Iranagh, Elham Amirzadeh; Abdul Rahman, Hejar; Motalebi, Seyedeh Ameneh (The Korean Nutrition Society and the Korean Society of Community Nutrition, 2016)
Background/objectives: Nutrition is a determinant factor of health in elderly people. Independent living in elderly people can be maintained or enhanced by improvement of nutritional behavior. Hence, the present study was conducted to determine the impact of Health Belief Model (HBM)-based intervention on the nutritional behavior of elderly women. Subjects/methods: Cluster-random sampling was used to assess the sample of this clinical trial study. The participants of this study attended a 12-week nutrition education program consisting of two (2) sessions per week. There was also a follow-up for another three (3) months. Smart PLS 3.5 and SPSS 19 were used for structural equation modeling, determination of model fitness, and hypotheses testing. Results: The findings indicate that intervention had a significant effect on knowledge improvement as well as the behavior of elderly women. The model explained 5 to 70% of the variance in nutritional behavior. In addition, nutritional behavior was positively affected by the HBM constructs comprised of perceived susceptibility, self-efficacy, perceived benefits, and barriers after the intervention program. Conclusion: The results of this study show that HBM-based educational intervention has a significant effect in improving nutritional knowledge and behavior among elderly women.